2004
DOI: 10.1093/molbev/msi043
|View full text |Cite
|
Sign up to set email alerts
|

CpG Mutation Rates in the Human Genome Are Highly Dependent on Local GC Content

Abstract: CpG dinucleotides mutate at a high rate because cytosine is vulnerable to deamination, cytosines in CpG dinucleotides are often methylated, and deamination of 5-methylcytosine (5mC) produces thymidine. Previous experiments have shown that DNA melting is the rate-limiting step in cytosine deamination. Here we show, through the analysis of human single-nucleotide polymorphisms (SNPs), that the mutation rate produced by 5mC deamination is highly dependent on local GC content. In fact, linear regression analysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
152
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(170 citation statements)
references
References 58 publications
16
152
1
1
Order By: Relevance
“…We further explored three potential factors that have been found to affect SNM mutation rate in non-MA experiments. First, local GC content is known to be associated with gene density, codon use, substitution rate, and mutation rate at CG sites (43,(46)(47)(48). We found no genome-wide correlation in mutation rate with local GC content in yeast, suggesting that GC contentrelated effects on substitution rate are largely due to postmutation selection or selection-like processes such as biased gene conversion.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…We further explored three potential factors that have been found to affect SNM mutation rate in non-MA experiments. First, local GC content is known to be associated with gene density, codon use, substitution rate, and mutation rate at CG sites (43,(46)(47)(48). We found no genome-wide correlation in mutation rate with local GC content in yeast, suggesting that GC contentrelated effects on substitution rate are largely due to postmutation selection or selection-like processes such as biased gene conversion.…”
Section: Discussionmentioning
confidence: 65%
“…However, a recent study using air chromatography found ∼0.364% methylation at cytosines in S. cerevisiae (42). If methylated cytosines in yeast have similar 10×-50× elevations in mutation rate as in humans (43)(44)(45), 1/5-1/25 of all CCG and TCG sites would have to be methylated for the observed ∼2× overall increase in mutation rate at these sites. Taking 0.364% to be the methylation rate in S. cerevisiae and assuming all methylation takes place within CCG and TCG contexts where we found elevated mutation rates, which correspond to ∼3% of the analyzed sequences, this value leads to an estimate of ∼1/22 of CCG and TCG sites being methylated.…”
Section: Discussionmentioning
confidence: 96%
“…GpC dinucleotides have the same C and G composition as CpG dinucleotides but are not targeted by DNA methylation (6,28). For this reason, GpC O/E often is used as an indicator of nucleotide composition bias while controlling for the influence of DNA methylation (22,29).…”
Section: Resultsmentioning
confidence: 99%
“…CpG dinucleotides are rare in the genome except in specific regions (CpG islands (19) ) and frequently undergo methylation. Two kinds of base transitions (C→T and G→A) underlie the two mutations that alone account for virtually all clinically observed mutations (R201C, R201H) of the GNAS gene in cases of FD/MAS.…”
Section: Both R201c and R201h Mutations Arise From Cytosine Methylationmentioning
confidence: 99%